Manipulation of the Immune System for Cancer Defeat: A Focus on the T Cell Inhibitory Checkpoint Molecules - D'Arrigo, Paolo; Tufano, Martina; Rea, Anna; Vigorito, Vincenza; Novizio, Nunzia; Russo, Salvatore; Romano, Maria F.; Romano, Simona (Current Medicinal Chemistry, 2020)
The immune system actively counteracts the tumorigenesis process; a breakout of the immune system function, or its ability to recognize transformed cells, can favor cancer development. Cancer becomes able to escape from immune system control by using multiple mechanisms, which are only in part known at a cellular and molecular level. Among these mechanisms, in the last decade, the role played by the so-called “inhibitory immune checkpoints” is emerging as pivotal in preventing the tumor attack by the immune system. Physiologically, the inhibitory immune checkpoints work to maintain the self-tolerance and attenuate the tissue injury caused by pathogenic infections. Cancer cell exploits such immune-inhibitory molecules to contrast the immune intervention and induce tumor tolerance. Molecular agents that target these checkpoints represent the new frontier for cancer treatment. Despite the heterogeneity and multiplicity of molecular alterations among the tumors, the immune checkpoint targeted therapy has been shown to be helpful in selected and even histologically different types of cancer, and are currently being adopted against an increasing variety of tumors. The most frequently used is the moAb-based immunotherapy that targets the Programmed Cell Death 1 protein (PD-1), the PD-1 Ligand (PD-L1) or the cytotoxic T lymphocyte antigen-4 (CTLA4). However, new therapeutic approaches are currently in development, along with the discovery of new immune checkpoints exploited by the cancer cell. This article aims to review the inhibitory checkpoints, which are known up to now, along with the mechanisms of cancer immunoediting. An outline of the immune checkpoint targeting approaches, also including combined immunotherapies and the existing trials, is also provided. Notwithstanding the great efforts devoted by researchers in the field of biomarkers of response, to date, no validated FDA-approved immunological biomarkers exist for cancer patients. We highlight relevant studies on predictive biomarkers and attempt to discuss the challenges in this field, due to the complex and largely unknown dynamic mechanisms that drive the tumor immune tolerance.
Keywords: V-domain Ig suppressor of T cell activation (VISTA)